Spatiotemporal characteristics analysis of multifunctional cultivated land: A case‐study in Shenyang, Northeast China. (2nd March 2020) - Qian, Fengkui; Chi, Yanru; Lal, Rattan
Abstract: The configuration of multifunctional cultivated land is critical for its protection. Although studies on multifunctional cultivated land have been conducted, there is a lack of information regarding the spatiotemporal characteristics and tradeoff synergy relationship of cultivated‐land functions at the same time on a nonadministrative unit scale. The purpose of this study was to analyze the spatial distribution characteristics and the tradeoff synergy areas from the perspective of multifunctional cultivated land for efficient use of land resources to minimize the conflict between people and nature. The fuzzy optimization model and spatial autocorrelation analysis method were used to study spatial distribution characteristics and the tradeoff synergy spatial patterns, respectively. The results showed that (a) the implementation of different improvement measures for the spatial distribution characteristics of cultivated‐land functions could also accelerate the coordinated development of cultivated‐land functions, (b) multiple functions of cultivated land not only had a synergy trend in time, but they also had a heterogeneity and fluctuation in spatial distribution, providing a direction for the new development or management pattern of cultivated land, and (c) results on the multifunctional evaluation and tradeoff synergy relationship of cultivated land provided the foundation for determining the short‐board function and upgrading direction of cultivated land. At the grid scale, the evolution of functional distribution characteristics and functional relationships are helpful for decision‐makers to implement accurately farmland protection policies and formulate farmland regulation rules.